Employers’ perception on skill competencies and the actual performance of bachelor of accounting graduates in Malaysia - Norman, Siti Norain; Abdul Latiff, Ahmed Razman; Mohd Said, Ridzwana (International Academic Institute For Science And Technology, 2018)
The concern over the skills of local accounting graduates is not new. Of late it has become a national issue when local accounting graduates are criticized for being incompetent in the workplace due to their lack of skills that are desired by employers. This study is undertaken with the aim of identifying the expectation-performance gap between employers’ perception and the actual performance of Malaysian Bachelor of Accounting graduates. It is based on a survey of employers in Malaysia. The data was collected through a mail questionnaire survey which taps the perceptions of employers from both audit and non-audit firm on fresh local accounting graduates. There were 16 types of skill competencies identified in this study. The result from t-test indicates that there is an expectation-performance gap between employers’ perception and actual performance of Bachelor of Accounting graduates. Bachelor of Accounting graduates’ actual performance is lower than what employers expect from them.